Music and mirroring : how music affects the mirror game - Buchkowski, Megan (2018)
Social bonding and intersubjectivity are basic human necessities, but have been notoriously difficult to measure. Recently, there has been an increased interest into research that utilises tools such as the mirror game (where two or more participants mirror each other’s arm movements) as a possible measure for these phenomena. The mirror game is a means to enter into shared leadership, a state where there is no designated leader of the movement and when intersubjectivity can be experienced. In the current study, the mirror game’s potential as a measure was investigated using music to facilitate social bonding between stranger dyads of equal musical standing. Participants were collected from the international community of the University of Jyväskylä, Finland, and were divided into pairs based upon a questionnaire. The dyads generated creative, synchronous motion jointly before and after one of three musical interventions (turn-taking, entrainment and solo). To determine if a relationship between the mirror game and social bonding was possible the velocity, acceleration and jitter of the arm movements in the shared leadership mirror game were analyzed. Social bonding was measured with the Inclusion of Other in Self scale (IOS, Aron, et at., 1992). The study found, through windowed cross-correlation, that the musical condition did have an impact upon how the shared leadership mirror game was played: turn-taking dyads showed more regulated, longer turns of leadership, whereas entrainment dyads showed an increase in periodic movement and solo dyads displayed no consistent relationship. The amount of jitter calculated in the post-intervention turn-taking mirror game trials was found to be significantly related to the IOS scores. A novel measure of social bonding using physical proximity was also investigated, but was not successful. It was concluded that the mirror game is able to capture some of the nonverbal aspects of human interaction and its sensitivity to changes in social bonding could lead to its use as a measurement tool.